First case report of Salmonella spp. infection in Homalopsis buccata snake: Laporan Pertama Kasus Infeksi Salmonella spp. pada Ular Homalopsis buccata - Tiara Wandira Hariyanto; Amelia, Ezanti Nur; Tyasningsih, Wiwiek; Rahmahani, Jola; Praja, Ratih Novita; Yudhana, Aditya; Nurwartanti, Maya; Fikri, Faisal (Universitas Airlangga, 2023)
Reptiles are a source of transmission of pathogenic bacteria to humans. Salmonella spp. are Gram-negative bacteria that are commonly found in the digestive tract of snakes. This study was conducted on Homalopsis buccata snakes with samples obtained by oral swabs and cloacal swabs on snakes. Isolation of Salmonella spp. carried out on Tetrathionate Broth media enrichment and will be inoculated on specific media in the form of Salmonella Shigella Agar media. Identification of bacteria was carried out by Gam staining and Indole, Methyl Red, Voges Proskauer and Citrate test. This study revealed the presence of Salmonella spp. in the snake Homalopsis buccata.